2023
DOI: 10.3847/1538-4357/acc58c
|View full text |Cite
|
Sign up to set email alerts
|

ELVES. III. Environmental Quenching by Milky Way–mass Hosts

Abstract: Isolated dwarf galaxies usually exhibit robust star formation but satellite dwarf galaxies are often devoid of young stars, even in Milky Way–mass groups. Dwarf galaxies thus offer an important laboratory of the environmental processes that cease star formation. We explore the balance of quiescent and star-forming galaxies (quenched fractions) for a sample of ∼400 satellite galaxies around 30 Local Volume hosts from the Exploration of Local VolumE Satellites (ELVES) Survey. We present quenched fractions as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 125 publications
4
7
0
Order By: Relevance
“…The average difference in quenched fractions between the two radial bins is ∼0.1 for UDGs and ∼0.2 for UPGs. This trend agrees with the findings in Greene et al (2023) and for normal satellites in the ELVES survey. From the bottom panels of Figure 5, we find that UDGs (UPGs) hosted by redder hosts also have a higher quenched fraction.…”
Section: Quenched Fractionssupporting
confidence: 92%
See 4 more Smart Citations
“…The average difference in quenched fractions between the two radial bins is ∼0.1 for UDGs and ∼0.2 for UPGs. This trend agrees with the findings in Greene et al (2023) and for normal satellites in the ELVES survey. From the bottom panels of Figure 5, we find that UDGs (UPGs) hosted by redder hosts also have a higher quenched fraction.…”
Section: Quenched Fractionssupporting
confidence: 92%
“…Using the FIRE-2 simulation, Samuel et al (2022) also showed that the quenched fraction increases as the distance to the host decreases, and hosts with higher CGM mass have more quenched satellites. Such trends are also found in observations (e.g., Greene et al 2023;. In Figure 4, by comparing UDGs and UPGs at two radial bins, we find a very similar trend that satellites that are closer to the host are more quiescent.…”
Section: Formation and Quenching Of Mass-size Outlierssupporting
confidence: 85%
See 3 more Smart Citations